Electronic market as a strategic lever of an innovation virtual system - an integrative approach to territorial innovations management - Giuseppina Passiante; Aldo Romano (European Regional Science Association (ERSA), 1998)
During the last years, electronic market has become established very quickly in all areas of the business world. Moreover, according to the most recent forecasts, it will grow exponentially during the years. ?Electronic market? phenomenon highlights the most significant effect of the Information and Communication Technologies development: space and time independence of the economic and social processes; every people, every social group, every Organization can communicate or can share information, knowledge, objectives, anywhere and anytime. In this new socioeconomic context, a re-thinking of local system economic growth models becomes necessary. In this paper we present Innovation Virtual System, as a new model for local systems development. Innovation System is conceived as a set of interacting Organizations, embedded in a dense web of social and economic relationships, skilled at creating, acquiring and transferring knowledge and at adapting their behavior according to knowledge about their external and internal settings. More specifically, we try to identify the effects of electronic market on these ?knowledge creating? Organizations, that is on their internal learning circuits and on their external relationships. Particularly we focus in the Internet based electronic market, highlighting the differences between Internet and the previous computing and communication environment, in order to give a clearer understanding of Internet as the strategic infrastructure of electronic market. After describing the impact of the Internet based electronic market on a single Organization, we present a framework of a local system collective learning process, and we describe some of the opportunities offered by the Internet based electronic market to this process.
Keywords: 330